CONCEPT AS A MEANS OF REFLECTING THE ESSENCE OF LINGUOMADANI WORLD VIEW (Academicia Globe: Inderscience Research, 2022)
In our view, the linguistic landscape of the universe implies the representation of landscapes formed in our imagination through the concepts of existence. This is what creates a clear picture of the objects and events in the environment. Ultimately, the linguistic landscape of the universe means that the object and event in that environment exist are re-expressed through linguistic means. In this article, we explored the importance of the concept as a means of reflecting the essence of the national-cultural worldview.